2021
DOI: 10.1155/2021/6681651
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Navigation Mark Floating Based on Fractional-Order Gradient Descent with Momentum for RBF Neural Network

Abstract: To address the difficulty of estimating the drift of the navigation marks, a fractional-order gradient with the momentum RBF neural network (FOGDM-RBF) is designed. The convergence is proved, and it is used to estimate the drifting trajectory of the navigation marks with different geographical locations. First, the weight of the neural network is set. The navigation mark’s meteorological, hydrological, and initial position data are taken as the input of the neural network. The neural network is trained and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Xu et al constructed an improved complex-valued neural network that uses latitude and longitude as inputs to predict the drifting position of anchored buoys [27]. Fang and Jauregui-Correa designed a fractional step decline model of a radial basis function (RBF) neural network with meteorological data, hydrological data, latitude, and longitude as inputs to predict the position of navigation beacons and obtained prediction results of high accuracy [28]. Moreover, in a recent study on trajectory prediction at sea, on one hand, it is found that hybrid multi-layer ANN-based models achieved better performance than a single-layer model [29][30][31].…”
Section: Related Workmentioning
confidence: 99%
“…Xu et al constructed an improved complex-valued neural network that uses latitude and longitude as inputs to predict the drifting position of anchored buoys [27]. Fang and Jauregui-Correa designed a fractional step decline model of a radial basis function (RBF) neural network with meteorological data, hydrological data, latitude, and longitude as inputs to predict the position of navigation beacons and obtained prediction results of high accuracy [28]. Moreover, in a recent study on trajectory prediction at sea, on one hand, it is found that hybrid multi-layer ANN-based models achieved better performance than a single-layer model [29][30][31].…”
Section: Related Workmentioning
confidence: 99%
“…Li et al [ 12 ] used a BP neural network (BPNN) to predict the drift position of buoy T10 in the Tonggu waterway. Fang [ 13 ] established a fractional-order gradient descent with the momentum RBF neural network algorithm to predict the drift value of buoy #4 in Xiamen port. Xu [ 14 ] proposed an improved complex-valued neural network to implement the drift position prediction of buoys 11A and No.…”
Section: Introductionmentioning
confidence: 99%